2017
DOI: 10.3390/nu9040323
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-Rich Diet Affects Mitochondrial DNA Damage and Repair in Rats

Abstract: Evidence indicates that many forms of fructose-induced metabolic disturbance are associated with oxidative stress and mitochondrial dysfunction. Mitochondria are prominent targets of oxidative damage; however, it is not clear whether mitochondrial DNA (mtDNA) damage and/or its lack of repair are events involved in metabolic disease resulting from a fructose-rich diet. In the present study, we evaluated the degree of oxidative damage to liver mtDNA and its repair, in addition to the state of oxidative stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 51 publications
4
50
0
Order By: Relevance
“…As before mentioned, oxidative stress is critically involved in NAFLD pathogenesis, because caused lipid peroxidation increasing ROS production. In particular, high fructose micro-environmental stimulates ROS formation [4,6,7,35] and this study confirmed the exacerbated ROS production not only in mitochondria, but also in other cytoplasm compartments (Fig. 4c).…”
Section: Representative Immunoblots Are Shownsupporting
confidence: 82%
See 1 more Smart Citation
“…As before mentioned, oxidative stress is critically involved in NAFLD pathogenesis, because caused lipid peroxidation increasing ROS production. In particular, high fructose micro-environmental stimulates ROS formation [4,6,7,35] and this study confirmed the exacerbated ROS production not only in mitochondria, but also in other cytoplasm compartments (Fig. 4c).…”
Section: Representative Immunoblots Are Shownsupporting
confidence: 82%
“…Numerous data suggest that chronic exposure to a highfructose microenvironment could lead to a decrease in the mitochondrial biogenesis and a concomitant increase in mitochondrial oxidative stress production [35] in hepatocytes.…”
Section: Representative Immunoblots Are Shownmentioning
confidence: 99%
“…Since there was no increased 4‐HNE and HEX formation in the stomach of sucrose‐fed compared to starch‐fed rats, the observed oxidative stress in sucrose‐fed rats is likely not a consequence of enhanced lipid oxidation during digestion. An alternative explanation may be the metabolic conversion of fructose to uric acid in the liver, which is accompanied by mitochondrial oxidative stress and dysfunction, and hepatic steatosis in rats . Indeed, in the present study, hepatic oxidative stress was observed in rats on the sucrose diets, indicated by the increased hepatic TBARS concentrations, along with increased liver weight and fat accumulation in the mesenterium and retroperitoneum.…”
Section: Discussionmentioning
confidence: 45%
“…Previously, it has been demonstrated that probiotic therapy with L. plantarum strains improves urinary oxalate, calcium, uric acid, creatinine and serum uric acid levels in rats with increased renal calcium oxalate deposition [35]. A diet rich in fructose can lead to the induction of marked oxidative stress and mitochondrial dysfunction [36]. Oxidative stress arising from a high-fructose diet has been shown to suppress antioxidant enzymes in different tissues [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%